2016
DOI: 10.3892/or.2016.5143
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase 2 facilitates lymphangiogenesis in breast cancer by regulating VEGF-D

Abstract: In our previous studies, sulfatase 2 (Sulf2) was found to upregulate vascular endothelial growth factor-D (VEGF-D) expression in breast cancer. As VEGF-D plays an important role in lymphangiogenesis, we hypothesized that Sulf2 facilitates lymphangiogenesis in breast cancer by regulating VEGF-D. To evaluate the functions of Sulf2 on lymphangiogenesis in breast cancer, proliferation, apoptosis, cell cycle, cell mobility and tube-formation of lymphatic endothelial cells (LECs) were measured in vitro. Lymphangioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Though VEGF-D has been reported as a lymphangiogenic factor, we found that VEGF-D showed significant promotion only to migration, but had little effect on the proliferation of LECs. This is similar to the results in previous studies 26 , 27 . We think that VEGF-D appears to be more important in migration rather than proliferation of LECs.…”
Section: Discussionsupporting
confidence: 93%
“…Though VEGF-D has been reported as a lymphangiogenic factor, we found that VEGF-D showed significant promotion only to migration, but had little effect on the proliferation of LECs. This is similar to the results in previous studies 26 , 27 . We think that VEGF-D appears to be more important in migration rather than proliferation of LECs.…”
Section: Discussionsupporting
confidence: 93%
“…Though VEGF-D has been reported as a lymphangiogenic factor, we found that VEGF-D showed signi cant promotion only to migration, but had little effect on the proliferation of LECs. This is similar to the results in previous studies 26,27 . We think that VEGF-D appears to be more important in migration rather than proliferation of LECs.…”
Section: Vegf-d Acts As a Ligand To Vegfr-2 Or -3 On The Cell Surfacesupporting
confidence: 93%
“…Western blot analysis was performed as previously described [ 29 ]. The primary antibodies used are as follows: phospho-AKT1 S473 (Abcam ab66138) [ 96 ], pan-AKT (Abcam ab8805) [ 97 ], β-Actin (Santa Cruz sc-47778), BCL-2 (Santa Cruz sc-509), phospho-cMET Y1234/1235 (Cell Signaling 3077S), cMET (Cell Signaling 8198S), phospho-cSRC Y416 (Santa Cruz sc-101802), cSRC (Santa Cruz sc-8056), phospho-EGFR Y1068 (Cell Signaling 3777S) [ 98 ], EGFR (Abcam ab2430) [ 99 ], phospho-p44/42 MAPK T202/Y204 (Cell Signaling 4370S) [ 100 ], p44/42 MAPK (Cell Signaling 4695S) [ 101 ], phospho-HER2/ neu Y1248 (Santa Cruz sc-12352-R) [ 60 ], HER2/ neu (Abcam ab2428) [ 102 ], phospho-HER3 Y1289 (Cell Signaling 4791S) [ 98 ], HER3 (Santa Cruz sc-415) [ 103 ], phospho-HER4 Y1284 (Cell Signaling 4757S) [ 104 ], HER4 (Santa Cruz sc-8050) [ 105 ], phospho-IGF1Rβ Y1135/1136 (Cell Signaling 3024S), IGF1Rβ (Cell Signaling 9750S), p27 kip1 (Cell Signaling 3686S), phospho-p65 S536 (Cell Signaling 3033S), p65 (Cell Signaling 4764S), phospho-STAT3 Y705 (Cell Signaling 9131S), STAT3 (Cell Signaling 9139S), and TFF3 (Abcam ab108599) [ 25 ]. The secondary anti-rabbit, anti-mouse and anti-goat horseradish peroxidase (HRP)-conjugated antibodies were obtained from Cell Signaling Technology.…”
Section: Methodsmentioning
confidence: 99%